Bilateral anterior ischemic optic neuropathy after bilateral neck dissection - María J Suárez-Fernández (Dove Medical Press, 2010)
María J Suárez-Fernández, Antonio Clariana-Martín, Enrique Mencía-Gutiérrez, Esperanza Gutiérrez-Díaz, Teresa Gracia-García-MiguelOphthalmology Department, 12 de Octubre Hospital, Complutense University, Madrid, SpainPurpose: The risk of visual loss after nonocular surgeries is very low, between 0.2% and 4.5%. According to the American Society of Anesthesiologists, ischemic optic neuropathy has been reported mostly after spinal surgery (54.2%), followed by cardiac surgery and radical neck dissection (13.3%). It may occur in association with some conditions that include systemic hypotension, acute blood loss and hypovolemia.Case report: A 46-year-old woman, whose diagnosis was laryngeal squamous cell carcinoma, complained of visual loss in her right eye two days after surgery (laryngectomy with bilateral radical neck dissection and left jugular ligature) and one day later in her left eye. The diagnosis was nonarteritic anterior ischemic optic neuropathy.Conclusion: Anterior ischemic optic neuropathy related to nonocular surgery is usually bilateral and its prognosis is very poor, resulting in blindness or severe visual loss. Although rare, patients should be warned about this complication, which has a profound impact on quality of life, since no therapeutic measure, including correction of hypotension and anemia, seems to improve the prognosis of this complication.Keywords: ischemic optic neuropathy, visual loss, radical neck dissection, blood loss